Constitutive expression of a stabilized transcription factor group VII ethylene response factor enhances waterlogging tolerance in wheat without penalizing grain yield. (11th February 2019) - Wei, Xuening; Xu, Huijun; Rong, Wei; Ye, Xingguo; Zhang, Zengyan
Abstract: Waterlogging causes oxygen deprivation within plant roots and affects crop growth and yield. In crop wheat ( Triticum aestivum ), molecular responses to waterlogging are poorly understood. Here, we performed a genome‐wide analysis of group VII ethylene response factor (ERFVII) genes in hexaploid wheat and identified 25 genes, which were induced by waterlogging with diverse manner. Among them, TaERFVII.1 exhibited differential expression patterns between waterlogging‐tolerant wheat Nonglin46 and susceptible wheat Yangmai16 under waterlogging. Constitutive expression of Ta ERFVII.1 with an MYC‐peptide tag at its N terminus in wheat enhanced tolerance to waterlogging as evidenced by increased grain weight per plant, survival rate, and chlorophyll content of leaves and by increased expression of waterlogging‐responsive genes, while silencing of TaERFVII.1 compromised the expression of waterlogging‐responsive genes. Notably, constitutive expression of the stabilized Ta ERFVII.1 did not negatively impact both plant development and grain yield under standard conditions. We further demonstrated that constitutive expression of stabilized Ta ERFVII.1 elevated the transcriptional level of TaSAB18.1, the ortholog of Arabidopsis HRA1 and rice SAB18, consequently reduced the expression of waterlogging‐responsive genes under standard conditions. These results suggest that TaERFVII.1 plays an important role in wheat tolerance to waterlogging, and it could be a candidate for improving crop waterlogging tolerance. Abstract : Waterlogging severely threatens crop production worldwide. In this study, we identified TaERFVII.1, one of group VII ethylene response factor (ERFVII) genes in hexaploid wheat and provides evidences for its role in enhancing waterlogging tolerance through both overexpression transgene in wheat and gene silencing. Importantly, constitutive expression of the stabilized Ta ERFVII.1 in wheat does not cause negative impacts on grain yield under standard condition. We further demonstrate that TaSAB18.1, the wheat ortholog of Arabidopsis HRA1 and rice SAB18, reduces transcription of waterlogging‐responsive genes in stabilized TaERFVII.1 ‐transgenic wheat under standard condition. TaERFVII.1 could be a gene target for improving crop tolerance to waterlogging using gene‐engineering or genome‐editing system.